Oral isotretinoin for the treatment of dermatologic conditions other than acne: a case series - Abdulrahman Janahi; Maria Alsannaa; Zahra Abdulla; Saad Alotaibi; Ameen Alawadhi; Jawaher Aljalahma (Dermatology Reports)
Dermatophyte infections, also known as tinea, along with viral warts, are common skin conditions that can be difficult to treat, especially when they recur or resist standard therapies. Isotretinoin, a medication traditionally used for acne, has recently shown promise as an adjuvant therapy for these conditions. This retrospective case-series study included four adult patients with persistent or recurrent tinea infections (tinea cruris and tinea corporis) or viral warts (genital and facial) who were treated with oral isotretinoin in addition to standard therapies. The patients’ demographics, clinical presentations, treatment regimens, and responses were analyzed. All four patients showed significant clinical improvement after starting isotretinoin. Two patients with viral warts achieved complete clearance, and two patients with tinea infections experienced notable improvement. No severe side effects were reported. This case series suggests that isotretinoin may be a promising adjunctive therapy for patients with persistent or recurrent tinea infections and viral warts. However, further quantitative controlled studies are needed to confirm these findings and establish optimal treatment protocols. This study provides preliminary evidence for the potential benefit of using isotretinoin as an adjunctive therapy for recalcitrant tinea infections and viral warts. Further research is warranted to explore its efficacy and safety in larger populations.